2019
DOI: 10.1080/02688697.2019.1648757
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nationwide referral pathways, investigation and treatment of suspected cauda equina syndrome in the United Kingdom

Abstract: Purpose: Cauda equina syndrome (CES) is a spinal emergency with clinical symptoms and signs that have low diagnostic accuracy. National guidelines in the United Kingdom (UK) state that all patients should undergo an MRI prior to referral to specialist spinal units and surgery should be performed at the earliest opportunity. We aimed to evaluate the current practice of investigating and treating suspected CES in the UK. Materials and Methods: A retrospective, multicentre observational study of the investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…'Scan-negative’ cauda equina syndrome is relatively common: a recent study involving 28 of the 30 UK neurosurgery centres found 4441 referrals for possible cauda equina syndrome over a 6-month period 11. A systematic review of cauda equina syndrome incidence and three scan-negative cauda equina syndrome studies found 69%–84% of patients referred as possible cauda equina syndrome had negative or non-explanatory scans, with no other neurological cause found 1.…”
Section: Who Gets Scan-negative Cauda Equina Syndrome?mentioning
confidence: 99%
“…'Scan-negative’ cauda equina syndrome is relatively common: a recent study involving 28 of the 30 UK neurosurgery centres found 4441 referrals for possible cauda equina syndrome over a 6-month period 11. A systematic review of cauda equina syndrome incidence and three scan-negative cauda equina syndrome studies found 69%–84% of patients referred as possible cauda equina syndrome had negative or non-explanatory scans, with no other neurological cause found 1.…”
Section: Who Gets Scan-negative Cauda Equina Syndrome?mentioning
confidence: 99%
“…Given the limited access to neurosurgical expertise in most countries, generalists are expected to care for an expanding volume of both pre-operative, post-operative and non-operative neurosurgical patients; for example, a recent study of traumatic brain injury patients in the UK revealed that only 17% of patients referred to the neurosurgical center were transferred for specialist management. [26][27][28] This can be particularly true in LMICs where neurosurgical provision is scarce. 4,5 Estimates show that the poorest third of the world's population receive only 3•5% of all major surgeries undertaken worldwide.…”
Section: Importance Of Exposure To Neurosurgical Education In Medical Schoolmentioning
confidence: 99%
“…In the past 4 years, NANSIG has established itself as a platform for members to collaborate and contribute to high-quality multi-centre research; some of which has informed national specialty reports [ 16 , 21 ]. To date, NANSIG has been involved in seven (three complete, four ongoing) national research, audit and quality improvement projects, with several in the process of being developed (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…of conference presentations No. of publications ENTICE [ 16 ] Retrospective study assessing adherence of cauda equina syndrome referrals to published national guidelines. Supported by the BNTRC 2016 2017 86 56 28 4441 2 1 STUN [ 14 ] Cross-sectional study of undergraduate neuroanatomy teaching in the UK and Ireland 2019 2020 11 6 24 N/A 1 1 ELISAR-GB Prospective evaluation of intraoperative surgical adjuncts used in the resection of glioblastoma tumours 2019 Ongoing 84 46 28 291 2 - SPICE-19 [ 5 , 8 , 34 ] Prospective observational study of mental health and well-being of medical students and foundation doctors during the COVID-19 pandemic 2020 2020 35 34 32 2075 10 4 CRANIAL [ 9 , 10 , 24 ] Prospective observational cohort study of cerebrospinal fluid rhinorrhoea rates after endonasal intervention to the skull base 2020 Ongoing 148 34 30 869 …”
Section: Introductionmentioning
confidence: 99%